Payments and Securities Settlement Systems in Pakistan - World Bank (Washington, DC, 2017)
The South Asia Payments and Securities Settlement Initiative (SAPI) objective is to describe and assess the payments and securities settlement systems of the countries of South Asia with a view to identifying possible improvement measures in their safety, efficiency and integrity. To assure quality and effectiveness, the SAPI includes two important elements. First, all studies are conducted with the active participation of country officials and the project builds on the existing work being undertaken in the respective countries. Second, the initiative draws on international and national expertise to provide guidance, advice and alternatives to current practices. This report, payments and securities settlement systems in Pakistan, is the first of the public reports in the SAPI series and was prepared with the active support of the State Bank of Pakistan. Economic developments in Pakistan during the last decade have-to a significant extent-been influenced by the Government's program for poverty reduction and the development of markets and the real economy. However, the economic development slowed down in 2008 and 2009, as the macroeconomic situation deteriorated significantly owing to adverse security developments, large price increase of some commodities such as oil and food, global financial turmoil, and national political and security issues. This strong macroeconomic performance resulted from the implementation of a series of important structural reforms. In the early 2000s, the government expanded the role of markets in the economy, privatized a number of large state-owned enterprises, established market-based regulatory bodies, and took steps to reduce the cost of doing business in Pakistan.